Spatial assessment of noise pollution levels at Princess Nourah bint Abdulrahman University - AlAmri, Eman Rafi; Salam, Thikra Abduljalil; Aljasser, Lameaah Abdulaziz (Journal of natural sciences, life and applied sciences, 2022)
The study evaluated noise at Princess Noura Bint Abdulrahman University in several vital sites. The main sources of noise were identified at peak times. The results are compared with WHO standards for noise levels. Twenty-nine observation sites were selected on campus based on different land uses. The measurements were monitored using sound level meter at 15 minutes intervals in the morning, noon, and in the evening for a week .The study used deductive approach and statistical model to predict the spatial data of noise. The results were analyzed using spatial interpolation models for spatial mapping of noise levels on the campus. Statistical analysis technique- inverse distance weighted- was used to perform a prediction-based spatial interpolation to complement the spatial data taken from the field. The noise measurements were monitored for dwellings, students, staff and trainee’s cars at women driving center as well as taxis, high noise levels are recorded above the standard limits in most specific points.This study recommends managing and monitoring noise pollution on campus and reset land uses to limit and reduce noise pollution. Despite the efforts of the university management in intensifying trees inside and outside the campus and building soundproof walls, it is recorded higher noise levels than allowed.
Keywords: Noise; pollution; sound level meter; Women's driving Center; Princess Nourah University